Manfaat Pembelajaran Tematik Terintegrasi Ilmu Keislaman bagi Perkembangan Psikologis Peserta Didik - Syaifudin, Syaifudin; Murti, Roso (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2023)
This article aims to explain the benefits of integrated thematic learning in Islamic sciences in the context of the psychological development of students. The research method used is descriptive, which involves a literature review of related studies and secondary data analysis. The results of the analysis show that integrated thematic learning of Islamic sciences has significant benefits for the psychological development of students. Among other things, it can increase understanding and awareness of moral and ethical values in the Islamic religion, strengthen students' Islamic identity, help improve students' social and emotional skills, and also provide relevant and meaningful contexts for student learning. In conclusion, by strengthening religious values, Islamic identity, social skills, and the relevance of learning, this approach can provide a holistic educational experience and prepare students to become individuals with integrity and psychological development.